Integrated Cultivation of Land-Sea Ecosystems That Prioritizes Harmony with Nature and Society - Cening Kardi; Putu Fajar Kartika Lestari (Eduvest - Journal of Universal Studies, 2024)
There is an urgent need for aquaculture systems that not only increase productivity, but also maintain ecological balance and improve the well-being of local communities. With increasing pressure on natural resources due to overexploitation, emerging climate change, and global economic uncertainty, new approaches that integrate terrestrial and marine ecosystems are crucial. This research aims to develop an integrated aquaculture model that prioritises harmony between nature and society. This approach incorporates organic farming and mariculture practices, in line with blue economy principles, to create environmental sustainability and social welfare. The research method used was descriptive qualitative, with a focus on mapping specific regional areas consisting of three or four agro-climatic regions. Data were collected through surveys and focus group discussions (FGDs), covering ecological factors such as climate, coastal plain quality, seabed and seawater. Seawater health estimation for mariculture was based on physical, chemical and biological parameters with APHA (1992) guidelines. The results show that this integrated aquaculture can improve environmental quality and productivity of land and sea, while creating harmony between natural resource management and social welfare. This model provides a practical solution to achieve sustainable development.